Recovery of crude oil from oily sludge in an oilfield by sophorolipid. (3rd July 2019) - Liu, Xiaonan; Yao, Tiantian; Lai, Ruiqiu; Xiu, Jianlong; Huang, Lixin; Sun, Shanshan; Luo, Yijing; Song, Zhaozheng; Zhang, Zhongzhi
Abstract: Oily sludge is a hazardous waste, so its improper disposal not only pollutes the environment but also endangers human health. In this study, following the principle of resource recycling, reduction and harmless treatment of oil sludge, we used sophorolipid, a biological surfactant, to wash and recover oily sludge in an oilfield. Then, the influence of technological parameters (such as concentration, temperature, mud liquid ratio, and stirring speed), on oil content in sediment was investigated. The lowest residual oil content was when sophorolipid－concentration was 0.05%, the temperature was 35 °C, the mud-to-liquid ratio was 1:3, the stirring speed was 350 r/min, and the stirring time was 2 h. The glycolipid surfactant showed potential industrial application value as it recovered 78.62% of the crude oil from the oily sludge and reduced the oil content of the sediment to less than 2%.